Effect of water storage on resin-dentin bond strengths formed by different bonding approaches - Martins G; Calixto A; Gomes OMM; Loguercio A; D′Alpino PHP; Reis A (Wolters Kluwer Medknow Publications, 2009)
Objectives: The purpose of this study was to evaluate the influence of water storage on resin-dentin bond strengths [µTBS] using different adhesive bonding approaches. Materials and Methods: Flat superficial dentin surfaces of 24 extracted human third molars were exposed and polished to create a standardized smear layer. The teeth were randomly distributed into four different groups: Three-step etch-and-rinse (Adper Scotchbond Multi-Purpose, 3M ESPE - SBMP), two-step etch-and-rinse (Adper Single Bond 2, 3 M ESPE - SB); two-step self-etch (AdheSE, Ivoclar/Vivadent - AD); and self-etch 1 step (Adper Prompt L-Pop, 3M ESPE - LP). Following the adhesive application (n = 6), resin composite was incrementally applied (Filtek™ Supreme XT - 3 M ESPE) in order to obtain bonded sticks, with a cross-sectioned area of 0.81 mm 2 . The bonded sticks were randomly divided and assigned to be tested after one day [OD] (n 30) or six months [6 M] of water storage [6 M] (n = 30). Results: Two-way ANOVA and Tukey′s test showed that none of the adhesives showed degradation after 6 M. SB achieved the highest µTBS both in the [OD] (49.13 MPa) and [6M] (40.27 MPa). Despite the highest values in both time evaluations, the µTBS of SB significantly reduced after 6M. LP showed the lowest µTBS in both periods of evaluation (18.35 and 18.34 MPa). Conclusions: Although a significant degradation was only observed for SB, this was the adhesive that showed the highest µTBS after 6 M of water storage.